Phase 1b/2 study of ibrutinib and lenalidomide with dose-adjusted EPOCH-R in patients with relapsed/refractory diffuse large B-cell lymphoma*. Issue 9 (29th July 2021) - Wilson, Wyndham H.; Phillips, Tycel; Popplewell, Leslie; de Vos, Sven; Chhabra, Saurabh; Kimball, Amy S.; Beaupre, Darrin; Huang, Da Wei; Wright, George; Kwei, Kevin; Ping, Jerry; Neuenburg, Jutta K.; et al.
Abstract: Relapsed/refractory diffuse large B-cell lymphoma (DLBCL) is difficult to cure; non-germinal center B-cell-like (non-GCB) and activated B-cell-like (ABC) DLBCL have worse outcomes than GCB DLBCL. Ibrutinib and lenalidomide are synergistic in vitro in ABC DLBCL and may augment salvage chemotherapy. In part 1 of this phase 1b/2 study (NCT02142049), patients with relapsed/refractory DLBCL received ibrutinib 560 mg and escalating doses of lenalidomide on Days 1–7 with DA-EPOCH-R (Days 1–5) in 21-day cycles. In part 1 ( N = 15), the maximum tolerated dose was not reached with lenalidomide 25 mg (recommended part 2 dose [RP2D]); most common grade ≥3 adverse events were anemia (73%) and febrile neutropenia (47%); the overall response rate (ORR) was 40%. At the RP2D ( n = 26), ORR was 71% in non-GCB and 64% in ABC. Ibrutinib and lenalidomide with DA-EPOCH-R had a manageable safety profile and antitumor activity in relapsed/refractory DLBCL, especially the non-GCB subtype.